Student satisfaction with hostel in international campus: A literature review - , Syarifah Hasanah; Idid, Syed Arabi; Harun, Aizul Nahar; Tareq, Mohammad Ali (Pontifícia Universidade Católica de São Paulo, 2017)
This paper adopts conceptual approach to understand on how uncertainty avoidance culture effects student satisfaction in the context of university housing. Most researchers postulate that Expectancy Disconfirmation Theory is the most suitable for assessing customer satisfaction. Paying attention to the issue of student accommodation satisfaction is the main concern to improve the performance of the services provided by student housing. Cultural value of the students is one of the contributing factors to their satisfaction. The present study only assesses the literature on Expectancy Disconfirmation Theory, customer satisfaction, student housing satisfaction, and link between uncertainty avoidance and customer satisfaction. This study significantly broadens the university‘s understanding of dealing with hostel residents from different cultures and helping provide quality services. This study is based on the Expextancy Disconfirmation Theory whereby the model has been reviewed in the context of international student accommodation with the findings that culture plays role in assessing the student satisfaction.